2005
DOI: 10.1056/nejmoa041668
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lenalidomide in Myelodysplastic Syndromes

Abstract: Lenalidomide has hematologic activity in patients with low-risk myelodysplastic syndromes who have no response to erythropoietin or who are unlikely to benefit from conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
542
1
14

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 815 publications
(574 citation statements)
references
References 28 publications
17
542
1
14
Order By: Relevance
“…A separate MDS entity involving only chromosome 5q, and the focus of the actin-sensing mechanism discussed below, is the former 5q-syndrome, now called MDS with isolated del(5q) (herein referred to as ((del)5 or 5q-)) (Vardiman et al, 2009). This syndrome is characterized by interstitial deletions in chromosome 5q (different than those found in AML) and commonly presents as anemia, mild leukopenia and thrombocytosis with a female predominance, and has a more benign clinical course and good response to lenalidomide (List et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A separate MDS entity involving only chromosome 5q, and the focus of the actin-sensing mechanism discussed below, is the former 5q-syndrome, now called MDS with isolated del(5q) (herein referred to as ((del)5 or 5q-)) (Vardiman et al, 2009). This syndrome is characterized by interstitial deletions in chromosome 5q (different than those found in AML) and commonly presents as anemia, mild leukopenia and thrombocytosis with a female predominance, and has a more benign clinical course and good response to lenalidomide (List et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…12 Clinical trials assessing the efficacy of lenalidomide in MDS showed that this drug can reduce transfusion requirements and reverse cytologic and cytogenetic abnormalities in patients who have MDS with the 5q31 deletion. 13,14 The aim of the present study was to apply the FISH technique in patients diagnosed with MDS in whom cytogenetic analysis had shown a normal karyotype, absence of metaphases or an abnormal karyotype without evidence of del(5q). FISH would allow the detection of the 5q deletion in those cases in which cytogenetic analysis had not found the deletion.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with MDS, the IPSS provides an estimated evaluation of life expectancy and transformation to AML that can vary from a few months to several years, according to the level of risk. 1 Among the current therapeutic options available for patients with lower risk MDS, it has been established that erythropoiesis-stimulating agents (ESAs), [6][7][8][9][10][11][12] immunomodulatory drugs like thalidomide and lenalidomide, [13][14][15][16][17][18][19] and immunosuppressive therapies 20,21 can at least partially restore hematopoiesis and induce transfusion independence in selected patients. However, with the possible exception of younger patients who are candidates for allogeneic stem cell transplantation, [21][22][23] transfusions and chelating therapy remain widely used treatment options for a large number patients.…”
mentioning
confidence: 99%